A qualitative study of contributing factors to burnout among Jordanian midwives - Alsaraireh, Arwa; Al-Sarairhe, Ishraq; Al-Tarawneh, Tamador R.; Raghavan, Divya; Al-Nawafleh, Ahmad H. (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The healthcare system, particularly the midwifery profession in Jordan, faces significant challenges that negatively impact midwives and the quality of maternal care, primarily due to resource limitations and increasing service demands. While quantitative research has examined burnout levels among Jordanian midwives, there is limited qualitative insight into their lived experiences, particularly in the southern region of Jordan. Objective: This study aimed to explore the factors contributing to burnout among midwives in southern Jordan and to gain a deeper understanding of their professional experiences within the current healthcare context. Methods: A qualitative descriptive approach was employed between 2023 and 2024. Ten midwives were purposively recruited from public hospitals and community health centers in southern Jordan. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis. Trustworthiness was ensured using Lincoln and Guba’s criteria: confirmability, credibility, dependability, and transferability. Results: Two main themes emerged from the analysis: 1) the emotional and physical toll of undervaluation and its negative impact on job satisfaction, and 2) limited professional autonomy and challenges related to empowerment in clinical settings. These findings reflect both personal and structural contributors to burnout. Conclusion: Burnout among midwives in southern Jordan is driven by emotional strain, lack of recognition, and restricted autonomy. These challenges affect not only job satisfaction but also the quality of care provided. Addressing these issues through supportive policies, improved working conditions, and greater professional recognition is critical for strengthening the midwifery workforce. The findings also offer valuable insights for other countries with similar healthcare structures and midwifery challenges.